MOTIVASI BELAJAR MAHASISWA PASCA PANDEMI COVID-19 - Nadya Shavira; Ganis Indriati; Jumaini Jumaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
The hybrid learning method is used as a learning method starting from second year of the pandemic period to the current post-pandemic. The implementation of learning with this method has an affects students' learning motivation. Learning motivation is a desire that arises in oneself as encouragement to carry out learning activities, so high learning motivation is very important to achieve good learning outcomes. The purpose of this study was to determine the description of student learning motivation after the Covid-19 pandemic. This study was a quantitative study with a descriptive method. The sampling technique was purposive sampling with 240 respondents. The measuring instrument used is the Motivated Strategies for Learning Questionnare (MSLQ) that have been tested for validity dan reability. The results of this study indicate that the majority of respondents are 17-25 years, female gender are 216 respondents (90,0%), year of college 2021 are 62 respondents (26,3%), status of residence boarding house are 168 respondents (70,0%), gadget used smartphone and laptop are 206 respondents (85,8%), and family income Rp. 3.000.000 – 6.000.000 are 102 respondents (42,5%). The results of learning motivation are categorized as high (78,3%). Student learning motivation after the covid-19 pandemic is in the high category, so it is expected that students can maintain learning motivation.Keywords: learning motivation, post covid-19 pandemic, university students